Preclinical Evaluation of a Novel Dual Targeting PI3Kδ/BRD4 Inhibitor, SF2535, in B-Cell Acute Lymphoblastic Leukemia - Ruan, Yongsheng; Kim, Hye Na; Ogana, Heather A.; Wan, Zesheng; Hurwitz, Samantha; Nichols, Cydney; Abdel-Azim, Nour; Coba, Ariana; Seo, Seyoung; Loh, Yong-Hwee Eddie; Gang, Eun Ji; Abdel-Azim, Hisham; et al. (Frontiers in Oncology, 2021)
The PI3K/Akt pathwayand in particular PI3Kδis known for its role in drug resistant B-cell acute lymphoblastic leukemia (B-ALL), and it is often upregulated in refractory or relapsed B-ALL. Myc proteins are transcription factors responsible for transcribing pro-proliferative genes, and c-Myc is often overexpressed in cancers. BRD4 is required for expression of c-Myc in hematologic malignancies including B-ALL. Previously, combination of BRD4 and PI3K inhibition with SF2523 was shown to successfully decrease Myc expression. However, the underlying mechanism and effect of dual inhibition of PI3Kδ/BRD4 in B-ALL remains unknown. To study this, we utilized SF2535, a novel small molecule inhibitor which can specifically target the PI3Kδ isoform and BRD4. We treated primary B-ALL cells with various concentrations of SF2535 and studied its effect on specific pharmacological on-target mechanisms such as apoptosis, cell cycle, cell proliferation, adhesion molecules expression using both in vitro and in vivo models. SF2535 significantly downregulates both c-Myc mRNA and protein expression through inhibition of BRD4 at the c-Myc promoter site and decreases p-AKT expression through inhibition of the PI3Kδ/AKT pathway. SF2535 induced apoptosis in B-ALL by downregulation of BCL-2 and increased cleavage of caspase-3, caspase-7, and PARP. Moreover, SF2535 induced cell cycle arrest and decreased cell counts in B-ALL. Interestingly, SF2535 decreased the mean fluorescence intensity (MFI) of integrin α4, α5, α6, and β1 while increasing MFI of CXCR4, indicating that SF2535 may work through inside-out signaling of integrins. Taken together, our data provide a rationale for the clinical evaluation of targeting PI3Kδ/BRD4 in refractory or relapsed B-ALL using SF2535.